On emerging economy sovereign spreads and ratings - Andrew Powell; Juan Francisco Martínez (Inter-American Development Bank, Research Department, 2008)
This paper analyzes alternative models for emerging sovereign ratings. Although a small number of economic fundamentals explain ratings reasonably well, variations in those economic fundamentals are themselves explained by a small number of world factors. On the other hand, global financial variables associated with risk aversion are additionally required in order to explain the significant spread compression at the end of 2006. To determine whether ratings matter for spreads, the paper compares results across different methodologies, in particular exploiting differences in opinion between rating agencies. The evidence from this and previous methodologies is that ratings do matter. Finally, the paper finds that global indicators of risk aversion have become less important for emerging market spreads and that the effect of sub-prime news is less than the effect of 'average news' on emerging economy credit default swap (CDS) spreads.
Keywords: F37; G14; G15; C23; 330; Ratings; Spreads; Panel Data; Länderrisiko; Ratingagentur; Zinsstruktur; Aufstrebende Märkte; Finanzmarkt